Effects of Intrauterine Infusion of Autologous Platelet-Rich Plasma in Women Undergoing Treatment with Assisted Reproductive Technology: a Meta-Analysis of Randomized Controlled Trials - Hu, Shifu; Jin, Zhishan; Tang, Qianqian (Geburtshilfe und Frauenheilkunde, 2022)
Purpose This meta-analysis was conducted to systematically retrieve relevant randomized controlled trials (RCTs) and evaluate the effects of intrauterine infusion of autologous platelet-rich plasma (PRP) in women with thin endometrium, implantation or pregnancy failure undergoing treatment with assisted reproductive technology (ART).Methods We conducted a systematic review and meta-analysis of the retrieved RCTs. Studies on the intrauterine infusion of PRP in women undergoing treatment with ART that were published in PubMed, the Cochrane library, Web of Science, and Embase from inception until June 2022 were included. The data were extracted and analyzed independently using the fixed-effects or random-effects model according to heterogeneity.Results Seven RCTs involving 861 patients (435 in the intervention group and 426 in the control group) were included. The rates of clinical pregnancy (risk ratio [RR]: 2.51; 95% confidence interval [CI]: 2.0–3.13; P < 0.00001), chemical pregnancy (RR: 1.96; 95% CI: 1.58–2.45; P < 0.00001), live births (RR: 7.03; 95% CI: 3.91–12.6; P < 0.00001), and implantation (RR: 3.27; 95% CI: 1.42–7.52; P = 0.005) were significantly higher in the women who received PRP infusion than in the control group. No significant differences were noted in the miscarriage rate (RR: 0.98; 95% CI: 0.39–2.42; P = 0.96) between the two groups.Conclusion In summary, intrauterine infusion of PRP may be an effective therapy for women with thin endometrium and recurrent implantation failure (RIF) undergoing treatment with ART. More population-based RCTs are warranted to verify the efficacy of our evidence.
Keywords: plättchenreiches Plasma (PRP); assistierte Reproduktionstechnologie; randomisierte kontrollierte Studien (RCTs)